Узагальнена структура приймача на базі DSP процесора - Литвиненко, О. В.; Білоцерківець, О. Г.; Мальцев, О. С. (ХНУРЕ, 2019)
Theoretical and experimental studies of the digital receiver onbased on the basis of the DSP signal processor, the possibility of constructing digital processing receivers is shown, a digital protocol receiver with a detailed description of components used in the radio is proposed. A new perspective direction of development of microelectronic digital and analogue digital elemental base and the emergence of new components allow the development of high-quality digital receivers principles of radio signal processing. DSP is a digital processor designed for special digital signal processing. At present, digital signal processing technologies receive the highest priority when developing new radio receivers. The implementation of these methods allows us to create more reliable and flexible systems. The value of systems using DSP is especially enhanced due to rough and unpredictable interference in the locations of the radio. The purpose of this article is to build a digital receiver based on the DSP signal processor.
Keywords: DSP; приймач; мікропроцесор; мікроконтролер; ЦАП